Analisis Implementasi Nilai Pendidikan Multikultural dalam Pembelajaran PPKN Kelas V Sekolah Dasar - Putri, Rossa Selfi Yuliana Putri; Kinanti, Anindyah Lyra Syashi; Fahmudita, Afika; Kharisma, Ahmad Ipmawan (Journal of Contemporary Issue in Elementary Education, 2024)
Multicultural education is important to prepare students to deal with diversity in society. This research aims to find out the implementation of the value of multicultural education in PPKN learning in Class V. The research method used is qualitative with a descriptive approach. The research subjects were elementary school students of SD Negeri 4 Made Lamongan class V. Data collection techniques include observation, interviews, and document analysis. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation. The results of the study include the school profile and respondents, implementation of multicultural values, implementation methods, student responses, and challenges faced. The main findings show that the values of respect for individual differences and religious tolerance are most frequently implemented. This study concludes that the implementation of multicultural values in Civics learning in elementary schools can be done effectively, even in a relatively homogeneous context. This result implies the need for curriculum development and learning methods that support multicultural education in various school contexts.